Genetic improvement of Pacific white shrimp [Penaeus (Litopenaeus) vannamei]: perspectives for genomic selection - Castillo-Juárez, Héctor; Campos-Montes, Gabriel R.; Caballero-Zamora, Alejandra; Montaldo, Hugo H. (Frontiers in Genetics, 2015)
The use of breeding programs for the Pacific white shrimp (Penaeus (Litopenaeus) vannamei) based on mixed linear models with pedigreed data are described. The application of these classic breeding methods yielded continuous progress of great value to increase the profitability of the shrimp industry in several countries. Recent advances in such areas as genomics in shrimp will allow for the development of new breeding programs in the near future that will increase genetic progress. In particular, these novel techniques may help increase disease resistance to specific emerging diseases, which is today a very important component of shrimp breeding programs. Thanks to increased selection accuracy, simulated genetic advance using genomic selection for survival to a disease challenge was up to 2.6 times that of phenotypic sib selection.